Analysis of the Use of Family Information System Applications for Family Planning Counselors in West Sumbawa Regency - Santana, Andi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The objectives of this research are: 1. To determine the development of the Family Planning (KB) Program in West Sumbawa Regency. 2. To analyze the effect of using the Family Information System application on the quality of Family Planning (KB) extension services in West Sumbawa Regency. This research uses a mix of methods, namely quantitative methodology using infere statistical analysis and qualitative methods using descriptive methods, where this research was conducted to fully or clearly describe the Family Information System Application Innovation for Family Planning Counselors in West Sumbawa Regency. There are generally two types of data, namely quantitative data and qualitative data which will be explained below. The author uses quantitative and qualitative data in carrying out this analysis. Data sources are all forms of information in the form of data. The population in this study were Family Field Officers (PLKB) or Extension Officers spread across 8 (eight) Districts of West Sumbawa Regency. In this study, the sample was 1 (one) person who was responsible as a Family Information System (SIGA) officer at the Family Planning Extension Office (PKB) in 8 (eight) sub-districts. Data collection procedures in research are documentation, questionnaires, interviews and observation. The research results show that the problem of delays in the distribution of monthly reports is a top priority to be resolved. In order for the distribution of this monthly report to run smoothly, the following steps need to be taken: education for data collection officers in villages and sub-districts about the importance of monthly reports being sent on time to districts so that PKB and District Data Managers can report to BKKBN on time, there needs to be supervision the process of sending monthly reports starts from the village, sub-district and district levels so that if problems occur they can be handled immediately, and increasing the number of data collection officers and data managers so that the data collection process can be carried out quickly so that monthly reports can be sent on time. Conclusion on the criteria for data management using the optimal SIGA application. The flow of data and reports from villages, sub-districts, districts and the center or vice versa can run on time and there are no data errors. Data processing officers understand how to use the SIGA application. Suggestions include: In order for the distribution of monthly reports to run optimally, support from data processing officers, internet networks and SIGA servers is needed, SIGA application data is valid, data checking, maintenance and backup processes are needed, efforts can be made to optimize data management using applications SIGA. Addition of data collectors and data managers who have an IT educational background. Periodic SIGA application training for data processing officers, the integration process of three subsystems, namely contraceptive services, field control and family data collection and SIGA application development must be completed immediately and increase the capacity and speed of the SIGA Server and increase internet connection bandwidth